A-32 Acute Concussive Symptom Profiles in Adolescents and Young Adults with History of Depression and Anxiety. (18th June 2020) - Presley, C; Meredith-Duliba, T; Tarkenton, T; Stokes, M; Miller, S; Bell, K; Batjer, H; Cullum, C M
Abstract: Objective: The aims of this study are (1) to examine the clinical symptom profiles of individuals with depression and/or anxiety history following a concussion and (2) to compare profile differences across groups. Method: Participants aged 12-25 (n=129, mean=15.6) with premorbid diagnoses of depression (n=24), anxiety (n=50), or depression+anxiety (n=55) were evaluated within 21 days after sustaining a concussion as part of the North Texas Concussion Registry (ConTex) using the Post-Concussion Symptom Scale (PCSS). Following the model described by Kontos and Collins (2014), symptom clusters were derived from the PCSS to create six domains (cognitive/fatigue, vestibular, ocular, posttraumatic migraine, anxiety/mood, cervical). ANOVAs with Tukey's post-hoc tests were conducted to compare domain symptom severity and total symptom severity across groups. Results: There were no demographic differences between groups. A single symptom profile was prominent across each group, with the primary, secondary, and tertiary symptomatic domains being posttraumatic migraine, ocular, and cognitive/fatigue, respectively. Across each domain the depression+anxiety group was most symptomatic, followed in order by the depression and anxiety groups. The depression+anxiety group reported significantly higher anxiety/mood (M=2.0 vs. M=1.3) and cognitive/fatigue (M=2.9 vs M=2.1) symptom severity compared to the anxiety group. Group differences on total symptom severity approached significance (F=2.83, p=.06). Conclusions: The observed symptom profiles suggest that the acute-concussive response is similar in adolescents and young adults with history of depression and/or anxiety. Multiple premorbid conditions, such as depression and anxiety, appear to magnify overall symptom severity. Further research is warranted to understand the relationship between symptom burden and premorbid mental health factors.